Macular Choroidal Thickness and Volume Measured by Swept-source Optical Coherence Tomography in Healthy Korean Children - Lee, Jung Wook (Korean J Ophthalmol, 2016)
PURPOSE: To evaluate the thickness and volume of the choroid in healthy Korean children using swept-source optical coherence tomography. METHODS: We examined 80 eyes of 40 healthy children and teenagers (<18 years) using swept-source optical coherence tomography with a tunable long-wavelength laser source. A volumetric macular scan protocol using the Early Treatment Diabetic Retinopathy Study grid was used to construct a choroidal thickness map. We also examined 44 eyes of 35 healthy adult volunteers (≥18 years) and compared adult measurements with the findings in children. RESULTS: The mean age of the children and teenagers was 9.47 ± 3.80 (4 to 17) vs. 55.04 ± 12.63 years (36 to 70 years) in the adult group (p < 0.001, Student's t-test). Regarding the Early Treatment Diabetic Retinopathy Study subfields, the inner temporal subfield was the thickest (247.96 µm). The inner and outer nasal choroid were thinner (p = 0.004, p = 0.002, respectively) than the surrounding areas. The mean choroidal volumes of the inner and outer nasal areas were smaller (p = 0.004, p = 0.003, respectively) than those of all the other areas in each circle. Among the nine subfields, all areas in the children, except the outer nasal subfield, were thicker than those in adults (p < 0.05). Regression analysis showed that age, axial length, and refractive error correlated with subfoveal choroidal thickness (p < 0.05). CONCLUSIONS: Overall macular choroidal thickness and volume in children and teenagers were significantly greater than in adults. The nasal choroid was significantly thinner than the surrounding areas. The pediatric subfoveal choroid is prone to thinning with increasing age, axial length, and refractive error. These differences should be considered when choroidal thickness is evaluated in children with chorioretinal diseases.